Effect of dietary inclusion of palm oil on feed consumption, growth performance and profitability of broiler - Rahman, MS; Akbar, MA; Islam, KMS; Iqbal, A; Assaduzzaman, M (Bangladesh Journal of Animal Science, 2012)
A total of 300 day-old Hubbard Classic broiler chicks were reared to investigate the effect of dietary inclusion of 2, 3, 4 and 5% of palm oil on feed consumption, growth performance and profitability of broiler. Addition of 4% palm oil in diet found to attribute additive effect on the growth of the bird from 2nd to 4th week of the trial. Broilers of 2 and 3% oil added group attained 1791g and 1777.67g live weight, respectively which was 4% and 3% higher than that of the control. Similar effect of different levels of palm oil was also observed in case of live weight gain. Dietary inclusion of palm oil improved feed consumption and significantly (P<0.05) higher feed consumption was recorded in 4% palm oil group than 5% oil group. From the economic analysis on production cost of broiler, it was found that total cost per broiler was the lowest in control group (Tk. 115.92), which was lower by Tk. 8.23, 7.46, 9.13 and 2.68 than the 2%, 3%, 4% and 5% oil added groups, respectively. Profit earned from each group (Tk/broiler and Tk/kg broiler) was statistically similar (P>0.05). It can be concluded that profitable broiler production might be possible without supplementation of palm oil. Key words: Broiler; Feed Consumption; Growth, Palm oil; Profitability DOI: http://dx.doi.org/10.3329/bjas.v39i1-2.9692 Bang. J. Anim. Sci. 2010, 39(1&2): 176-182